K2-99 revisited: a non-inflated warm Jupiter, and a temperate giant planet on a 522-d orbit around a subgiant. Issue 4 (2nd December 2021) - Smith, A M S; Breton, S N; Csizmadia, Sz; Dai, F; Gandolfi, D; García, R A; Howard, A W; Isaacson, H; Korth, J; Lam, K W F; Mathur, S; Nowak, G; et al.
ABSTRACT: We report new photometric and spectroscopic observations of the K2-99 planetary system. Asteroseismic analysis of the short-cadence light curve from K2 's Campaign 17 allows us to refine the stellar properties. We find K2-99 to be significantly smaller than previously thought, with R ⋆ = 2.55 ± 0.02 R⊙ . The new light curve also contains four transits of K2-99 b, which we use to improve our knowledge of the planetary properties. We find the planet to be a non-inflated warm Jupiter, with R b = 1.06 ± 0.01 $\mathrm{R_{\rm Jup}}$ . 60 new radial velocity measurements from HARPS, HARPS-N, and HIRES enable the determination of the orbital parameters of K2-99 c, which were previously poorly constrained. We find that this outer planet has a minimum mass M c sin  i c = 8.4 ± 0.2 $\mathrm{M_{\rm Jup}}$, and an eccentric orbit ( e c = 0.210 ± 0.009) with a period of 522.2 ± 1.4 d. Upcoming TESS observations in 2022 have a good chance of detecting the transit of this planet, if the mutual inclination between the two planetary orbits is small.